Analytic geometry - Sirug, Winston S. (Intramuros, Manila : Mindshapers Corporation, Incorporation, 2015)
Analytic Geometry is designed to give background in constructive mathematics taught in most pure and applied mathematics and other related programs in college and universities. The text's primary objective is to develop the student's understanding of the basic mathematical concepts and procedures needed to succeed in the field of mathematics, engineering, accountancy, information technology, computer science, business education, and other related fields.
Chapter 1. Fundamental Concepts -- Chapter 2. The Straight Line -- Chapter 3. Circles -- Chapter 4. Parabola -- Chapter 5. Ellipse -- Chapter 6. Hyperbola -- Chapter 7. Transformation of Coordinates -- Chapter 8. Polar Coordinates.
Keywords: GEOMETRY -- ANALYTIC